Calidad de cartera del Sistema Bancario y el Ciclo Económico. - Rebaza Vargas, Wilson Tealdo Martin (2011)
The economic literature concerned with the study of banking crises usually focuses on the particular characteristics of institutions that have gone bankrupt or weaknesses in supervisory and regulatory systems. An additional aspect that may help complete the analysis is to include the effect of macroeconomic factors. In fact, the quality of the institutional and regulatory framework and macroeconomic factors are interrelated insofar as there is a strong regulation and supervision, the banking system can adequately support a deteriorating macroeconomic situation. In this sense, this paper assesses the impact of economic growth in the state of bank solvency, as well as the effects on the vulnerability of the system arising from processes of bank credit boom, using series estimation methods of time and cross section. Among some results have The quality of the portfolio of bank loans in Peru is negatively correlated with the cycle of economic activity. Thus, booms or positive growth rates tend to improve credit quality, contrary to what happens in a downturn. However, the resulting elasticity is small, why growth rates require high or significant periods of growth or recession in order to observe a significant impact on delinquency of PBI.